Energy Sector Reform and the Pattern of the Poor : Energy Use and Supply, A Four Country Study - Botswana, Ghana, Honduras and Senegal - Prasad, Gisela (World Bank, Washington, DC, 2014)
This project had the following objectives: to undertake a detailed assessment for four countries of the steps taken to reform the energy sector and their impact (or not) on various groups of poor households; to identify patterns of energy use by poor households in various situations; to identify patterns of supply of energy to poor households; and to identify links between the supply and the use of energy by poor households, which are capable of being directly impacted by sector reform. Such links include: the actual use of various sources of energy (e.g. electricity); the form in which the source is used (e.g. battery or grid connection); its associated cost (capital costs and fuel costs); and the nature of the delivery form (state utility or local off-grid company, retailer of batteries or of LPG). The design of a template for future assessment of the impact of sector reform on the poor in other countries. Through the use of local consultants, wherever possible, the engagement in capacity building for economic and policy analysis of the energy sector.